Efecto neuroprotector del extracto hidroalcohólico de Piper aduncum “matico” en un modelo in vitro de neurodegeneración - Zaa, César (2012)
During the neurodegenerative processes there is a reduction of the function and viability of neurons. The pathological increase in the intracellular calcium concentration, the alteration of the synaptic plasticity and the apoptosis are implicated in Alzheimer disease (AD, a paradigm of a neurodegenerative process, related with the progressive loss of cognitive functions. To evaluate neuroprotector effect of Piper aduncumdamage was induced with Aβ1-42 and NMDA to cultured cells. So hippocampal cells were treated with Aβ 1-42 1 uM and cellular viability, levels of caspasa-3 and expression of NMDA receptors in synapses were evaluated. Also, intracellular calcium influxe (sobreestimulation with NMDA) of was registered in treatments with P. aduncum. In the neuroprotector evaluation there is a reduction of 20.6% of caspasa-3; one increase of 9.6% over control and recovery of 20.86% for NR1 and SV2 proteins respectively. Besides, there is a reduction of more than 50% of cellular calcium. These results demonstrate neuroprotector effect of P. aduncumfor the studied model.